2021
DOI: 10.1108/jabs-05-2021-0214
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable recovery for digital entrepreneurs with shared resources: enablers, challenges and solutions

Abstract: Purpose The purpose of this study is to identify important criteria for sustainable recovery of digital entrepreneurship from distress situation using shared resources. During pandemic disruption, the importance of sharing economy in managing business efficiency is reflected through this research. Design/methodology/approach The present study advances the knowledge on shared resources in business by integrating case study approach with multi criteria decision-making (MCDM) model. A fuzzy analytic hierarchy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The development and use of digital technologies create new opportunities for entrepreneurs (Fernandes et al 2022), enabling new businesses' development and business improvement that ensure economic, environmental, and social sustainability (Baran and Berkowicz 2021;George et al 2021;Gregori and Holzmann 2020;Jha et al 2022;Tim et al 2021;Tohănean et al 2020). That is, these technologies support digitization, digitalization, and digital transformation, which breaks with the past and leads to new sustainable growth business models (Gavrila and Ancillo 2022).…”
Section: Digital Entrepreneurship and Sustainabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The development and use of digital technologies create new opportunities for entrepreneurs (Fernandes et al 2022), enabling new businesses' development and business improvement that ensure economic, environmental, and social sustainability (Baran and Berkowicz 2021;George et al 2021;Gregori and Holzmann 2020;Jha et al 2022;Tim et al 2021;Tohănean et al 2020). That is, these technologies support digitization, digitalization, and digital transformation, which breaks with the past and leads to new sustainable growth business models (Gavrila and Ancillo 2022).…”
Section: Digital Entrepreneurship and Sustainabilitymentioning
confidence: 99%
“…Digital technologies in business activities not only bring better use of scarce resources, but also provide opportunities for sustainable innovations. In other words, the integration of digital technologies with entrepreneurship results in sustainable entrepreneurship and in the development of innovative business models (Gössling and Hall 2019;Gregori and Holzmann 2020;Jha et al 2022), supporting the transition from the linear economy to a circular economy (Manea et al 2021).…”
Section: Cluster 3 (Red Cluster): Sustainability and Sustainable Deve...mentioning
confidence: 99%
See 2 more Smart Citations
“…The second article explored 13 critical sustainable recovery measures for transportation systems and found that efficient traffic management, sustainability-focused policies, sensitization of stakeholders, financial support and adoption of 4 R practices are important for a sustainable recovery in freight transportation systems (Dwivedi et al , 2021). The third article analyzed enablers, challenges and solutions for sustainable recovery for green entrepreneurs and found that technological innovation, technology expertise, convergence of virtual and physical spaces, collaboration rather than competition and benefits to underserved groups through transparency are the most critical enablers for sustainable recovery (Jha et al , 2021). The fourth article discussed the impacts of the COVID-19 pandemic on micro, small and medium enterprises.…”
Section: Green Recovery Through Sustainable Supply Chains: Implicatio...mentioning
confidence: 99%